Gambaran Dukungan Keluarga Terhadap Pasien Riwayat Covid-19 Di Wilayah Puskesmas Kasihan 1 Bantul - Hidayati, Laili Nur; Nesyifa, Nada (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Introduction: The Kasihan Health Center in the Bantul area is one of the health center sociality that provides services and inpatient care for COVID-19 patients, in the past year there were 2,300 positive confirmed cases of COVID-19 19. People with COVID-19 have limitations in sociality because they have to carry out isolation both independently and medically at the hospital. Forms of family support are needed in this case because family support has a positive impact on the psychosocial problems of patients who are in the recovery stage. Patients feel much better due to the provision of psychosocial treatment which includes family interventions, social skills training, and so on. Research Objectives: To find out the form of family support for patients with a history of COVID-19. Method: Quantitative research method with a descriptive approach. Sampling using purposive sampling technique a number of 99 respondents. The research instrument used a family support questionnaire. Results: The results of the study found that almost all of the family support data for patients with a history of COVID-19 were included in the high support category, namely 90 respondents (90.9%). Conclusion: The majority of respondents provide very high family support, which means that the role as a family is fulfilled and given well in four categories, namely emotional, instrumental, informational, and esteem support, so that patients feel loved and loved by their loved ones